STUDY OF UTILIZATION OF FACILITIESFISHING PORT TANJUNG TIRAM KABUPATEN BATUBARA PROVINCE SUMATERA UTARA - Karlina, Noni; Syaifuddin, Syaifuddin; Bustari, Bustari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRAK This research was conducted in May 2018 at Fishing Port TanjungTiram by using a survey method. Data analysis used facility requirements analysis and facility utilization analysis. The facilities available at PP TanjungTiram are basic facilities, functional facilities, and supporting facilities. Of the 10 facilities available at PP TanjungTiram, 3 facilities are calculated for utilization, namely the loading dock length at pier II because loading and unloading activities of fishing boats are only carried out at dock II, port pool area, and the depth of the port pool. It was obtained that PP TanjungTiram dock utilization rate of fisheries activities amounted to 81,46%, meaning that the facilities in the category were utilized, the utilization rate of the port pond area was 57.72%, it could be said that the utilization rate was classified as underutilized while the depth of the port pool had a utilization rate of 114,28% so it can be concluded that the utilization rate for the port pool is included in the highly utilized category. Keywords:Fishing Port, Tanjung Tiram, utilization of facilities